The Role of Parents in Handling Children Challenges of Modern Times - Muhammad Hilmi Farras; Hafidz; Aisha Rahmawati; Angel Laveda Winsome Permata Samudra; Hadar Azizi; Aqila Fauziah Arimbi; Wais Alqorni (Bulletin of Islamic Research, 2025)
This study examines the critical role of parents in addressing the challenges faced by children in modern times. The rise of media and technology has posed significant challenges to character education, which is essential in shaping a child's emotional intelligence (EQ) and spiritual intelligence (SQ). Parents, as the primary educators, play a dominant role in instilling positive habits, providing a strong moral foundation, and fostering a religious atmosphere at home and school. The problem identified is that many parents inadvertently exacerbate these challenges by granting their children unrestricted access to gadgets at an early age, potentially hindering their character development. The research aims to explore how parental involvement, grounded in tenderness, affection, and Islamic principles, can effectively mitigate the adverse effects of technological advancements on children's upbringing. The study employs a qualitative research method through literature review and document analysis to gather insights into best practices and challenges faced by parents in modern parenting. The findings highlight that a proactive and balanced approach by parents, which includes setting boundaries on gadget usage, promoting religious values, and encouraging productive habits, significantly contributes to the development of EQ and SQ in children. This research underscores the importance of parental guidance in navigating the complexities of modern times and provides recommendations for fostering well-rounded and morally grounded individuals.